2013
DOI: 10.1155/2013/275037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nanoparticles Percentage on Mechanical Behavior of Silica-Epoxy Nanocomposites

Abstract: Silica-epoxy nanocomposites are very common among nanocomposites, which makes them very important. Several researchers have studied the effect of nanoparticle’s size, shape, and loading on mechanical behavior of silica-epoxy nanocomposites. This paper reviews the most important research done on the effect of nanoparticle loading on mechanical properties of silica-epoxy nanocomposites. While the main focus is the tensile behavior of nanocomposite, the compressive behavior and flexural behavior were also reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 68 publications
0
48
0
Order By: Relevance
“…6). This agglomeration generated stress concentration at the agglomerated particles and decreased the mechanical properties of the PMMA matrix [23][24][25] . Thus, the FS in the groups containing >1% silanized NPs was reduced, however, there was no significant differences in FM between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…6). This agglomeration generated stress concentration at the agglomerated particles and decreased the mechanical properties of the PMMA matrix [23][24][25] . Thus, the FS in the groups containing >1% silanized NPs was reduced, however, there was no significant differences in FM between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Welldispersed silica nanoparticles stiffen and toughen an epoxy adhesive more efficiently than silica microparticles owing to their larger surface-to-volume ratio, forming a more substantial matrix-filler interface area at a given weight fraction [1][2][3][4][5][6][7]. However, without any treatment, high-silica-content nanoparticles are difficult to disperse uniformly using a conventional mechanical mixer and tend to aggregate/agglomerate in the epoxy matrix [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Silica nanoparticles stiffen epoxy efficiently at low-strainrate loading [19]. Islam et al [7] showed that dynamic stiffness increases with silica particle content dispersed in the epoxy matrix. However, such studies focused on single-size silica-filled epoxy dynamic behavior at high-strain-rate loading.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, with the rapid progress in nanotechnology, nano‐sized inorganic particles are also of great interest for improving material properties . It has been reported that the dielectric strength can be increased by incorporation of nano‐sized fillers in an epoxy matrix .…”
Section: Introductionmentioning
confidence: 99%